Volatile Organic Compound (VOC) Reduction from Face Mask Wastes via a Microwave Plasma Reactor - Raynard Christianson Sanito; Marcelo Bernuy-Zumaeta; Hsi-Hsien Yang; Ya-Fen Wang (Aerosol and Air Quality Research)
Abstract Since the outbreak of the COVID-19 pandemic, the driven of face masks as personal protective equipment has increased significantly. Thus, disposed face masks from users should be handled properly for preventing the contamination of medical waste and the potential spread of viruses to the environment. This study gives information for dealing with face masks and assessing the volatile organic compounds (VOCs) concentrations via an atmospheric-pressure microwave plasma reactor. Face mask samples were mixed with the flux agents, namely cullet/glass, Al2O3, SiO2 and CaCO3. Samples were compared with control (no addition of flux agents) and the addition of only cullet. Moreover, microwave power, gas flow rate and pyrolysis duration were controlled at 1000 W, 9 standard liter per minute (SLM) and 5 min, respectively. The total concentration of VOC with the absence of flux agents was 448.04 ppm. Furthermore, the fuse of cullet and SiO2-Al2O3-cullet in the mask reduced the concentration of VOCs by 314.77 ppm and 54.7 ppm, respectively. Furthermore, the combination of CaCO3-SiO2-Al2O3-cullet creates the vitrification of material with the presence of crystalline structure, where the compositions of Ca and Si were 13.55% and 19.12%, respectively. Moreover, the final composition of carbon from the flux agents was 17.92 ± 10.08%. This study confirms that the fuse of CaCO3-SiO2-Al2O3-glass/cullet reduced the VOC via plasma technology, which is a promising method to be implemented in order to reduce the concentration of VOC from the face mask waste.